Emerging Vibrio vulnificus-Associated Infections After Seawater Exposure—Cases from the Bulgarian Black Sea Coast - Stephanie Radeva; Stoyan Vergiev; Georgi Georgiev; Denis Niyazi (Medicina)
Objectives: The aim of the current report is to present three cases of necrotizing fasciitis and sepsis caused by Vibrio vulnificus on the Bulgarian Black Sea coast. Materials and Methods: Two of the patients are males, 70 and 86 years of age, respectively, and one is an 86-year-old female. Data were collected from the patients’ examination records. V. vulnificus was isolated on 5% sheep blood agar from wound and blood samples and identified by the automated system Phoenix M50 (BD, Franklin Lakes, NJ, USA). Antimicrobial susceptibility was tested with two well-known methods (disk diffusion and broth microdilution). Results: All of the patients were admitted to our hospital due to pain, swelling, ulceration, and bullae on the legs and were febrile. They underwent surgery and received intensive care support. One of the patients developed septicemia and septic shock; one of his legs was amputated, but the outcome was fatal. The other patient received immediate approptiate antibiotic and surgical treatment, and the outcome was favorable. The third patient underwent emergency fasciotomy but died a few hours after admission. Conclusions: Global climate change is affecting the distribution of Vibrio spp., and their incidence is expected to increase. It is important to highlight the need for awareness among immunocompromised and elderly patients of the potential threat posed by V. vulnificus infections.